RUTAS TURISTICAS : ALTERNATIVA PRODUCTIVA ECOSOCIAL PARA LA GESTION SOSTENTIBLE DE MICROCUENCAS ALTO ANDINAS ESTUDIO DE CASO: LA RUTA PURINA KUNAN EN LA PROVINCIA DE CHIMBORAZO – ECUADOR - Jácome, Eduardo Muñoz; Esparza, Daniela; Gaibor, Verónica; Torres, Cristina (European Scientific Journal, ESJ, 2014)
The main feature is that Ecuador has a high degree of both natural and cultural biodiversity, making it a tourist power. The province of Chimborazo located at altitudes ranging from 156 m in the canton Cumandá , to 6310 meters above sea level ( Autonomous Government decentralized Chimborazo;2011) presents various climatic zones and living areas, this allows the promotion of tourism activities in all geographic areas, as part of it, is the watershed of the river Chimborazo, high rural territory Andean featuring attractions that are visited , in the case of Mount Chimborazo, the highest in the country and the fauna reserve of the same name, another highly crowded near and permanently, space is the population of Guano, for its craft and culinary production, however the indigenous communities in the watershed do not benefit from these visits , because they are not articulated to these tourist magnets, despite having other unique cultural and natural resources. The tourist route Kunan Purina, is a sustainable tourism product, which was designed in participation with the indigenous population represents 93 % of the population of the watershed of the river Chimborazo , craftspeople and other tourism stakeholders Guano city, given by aside the tourist potential of its territory and furthermore, the trends and demands of tourism. The Kunan Purina commercial analysis shows that the tourist route has accepted concept , because through this study, it is determined that there is a high unmet demands . The activities envisaged to be developed in the same according to the tastes and preferences of potential tourists are compatible with the tourist potential of the area and thus from the territory can offer in relation to culture and nature. From the results of this investigation it is concluded that the creation of tourist routes contributes to the link between rural and urban communities to benefit economically and socially ; under the criteria of equity, favoring social and territorial cohesion; contributes to the conservation of the environment , the identity of their populations and the Good Life , is demonstrated, then the path concept constitutes an ecosocial productive alternative for sustainable management of Andean watersheds.